Metal-free visible light photoredox enables generation of carbyne equivalents via phosphonium ylide C–H activation - Das, Mrinmoy (2019)
Carbyne, an interesting synthetic intermediate, has recently been generated from hypervalent iodine precursors via photoredox catalysis. Given the underexplored chemistry of carbyne, due to the paucity of carbyne sources, we are intrigued to discover a new source for this reactive species from classical reagents – phosphonium ylides. Our novel strategy employing phosphonium ylides in an olefin hydrocarbonation reaction features a facile approach for constructing carbon–carbon bonds through metal-free and benign reaction conditions. Moreover, the hydrocarbonation products were delivered in a highly regioselective manner.